Shape influence on the ultrafast plasmonic properties of gold nanoparticles - Peckus, Domantas; Tamulevičienė, Asta; Mougin, Karine; Spangenberg, Arnaud; Vidal, Loic; Bauerlin, Quentin; Keller, Marc; Henzie, Joel; Puodžiukynas, Linas; Tamulevičius, Tomas; Tamulevičius, Sigitas (Optics express, 2022)
The aim of shape-controlled colloidal synthesis of gold (Au) is to produce Au nanoparticles (NPs) with fine control of shapes, sizes, and dispersities. We show how transient absorption spectroscopy (TAS) can be used to rapidly and accurately quantify the vast ensemble of shapes of Au NPs in solution within minutes, including the synthesized nanorods, decahedra, and nanospheres. Colloidal solutions containing Au NPs were measured in TAS and their localized surface plasmon resonance (LSPR) modes were classified according to the shape, wavelength and number of peaks. Then their excited-state relaxation dynamics were used to ascertain their electron-phonon ( e-ph ) coupling time constant and frequency of optomechanical modes. TAS can quickly show that an Au nanosphere sample contains a tiny fraction of Au nanorods, whereas steady-state absorbance is totally blind to the presence of nanorods. Additionally, the TAS experiments indicate that the characteristic e-ph coupling time constants in Au nanorods depend on the NPs dimensions at high excitation intensity (> 6 µJ/cm 2 ) which can help identify if there are any elongated Au NPs in Au spheres samples. Finally, optomechanical oscillations formed by NPs breathing modes were observed, providing information related to the average size and monodispersity of Au nanospheres and nanorods.